2022
DOI: 10.3390/nu14030534
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Glaucoma with Natural Products and Their Mechanism of Action: An Update

Abstract: Glaucoma is one of the leading causes of irreversible blindness. It is generally caused by increased intraocular pressure, which results in damage of the optic nerve and retinal ganglion cells, ultimately leading to visual field dysfunction. However, even with the use of intraocular pressure-lowering eye drops, the disease still progresses in some patients. In addition to mechanical and vascular dysfunctions of the eye, oxidative stress, neuroinflammation and excitotoxicity have also been implicated in the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 264 publications
(289 reference statements)
0
56
0
Order By: Relevance
“…For these reasons, the search for natural products with anti-inflammatory activity has been the subject of several studies. Among them, EVOO phenolic compounds have been well proven for their anti-inflammatory activity [7,[77][78][79][80][81]. In this regard, in our previous work, we extensively reported and discussed the close correlation between the chemical characterization of EVOO polyphenols, anti-inflammatory potential, and biological activities in human studies [80].…”
Section: In Vitro Antioxidant and Anti-inflammatory Evoo Polyphenols ...mentioning
confidence: 92%
“…For these reasons, the search for natural products with anti-inflammatory activity has been the subject of several studies. Among them, EVOO phenolic compounds have been well proven for their anti-inflammatory activity [7,[77][78][79][80][81]. In this regard, in our previous work, we extensively reported and discussed the close correlation between the chemical characterization of EVOO polyphenols, anti-inflammatory potential, and biological activities in human studies [80].…”
Section: In Vitro Antioxidant and Anti-inflammatory Evoo Polyphenols ...mentioning
confidence: 92%
“…It is a potent antioxidant and protective agent, and its effects have been shown in neurodegenerative diseases, including Leber Hereditary Optic Atrophy, Parkinson’s disease, and Huntington’s diseases [ 25 , 26 ]; it also has an effect on retinal ganglion cells (RGCs) [ 27 ]. In preclinical trails [ 28 , 29 , 30 ], topically administrated CoQ 10 helped reduce the levels of extracellular glutamate, retinal damage, and cellular apoptosis. Treatment with the active form of CoQ 10 —ubiquinol—also enhances the survival rate of RGCs by decreasing apoptosis and increasing the expression of TFAM/oxidative phosphorylation (OXPHOS) complex 2 protein [ 25 , 28 ].…”
Section: Nutrition Blood Nutrient Levels Of Oxidative Stress and Glau...mentioning
confidence: 99%
“…Treatment with the active form of CoQ 10 —ubiquinol—also enhances the survival rate of RGCs by decreasing apoptosis and increasing the expression of TFAM/oxidative phosphorylation (OXPHOS) complex 2 protein [ 25 , 28 ]. CoQ 10 along with α-tocopherol (vitamin E) in POAG patients improved the retinal biometric responses (pattern electroretinogram improvement) and bioelectric cortical responses (visual evoked potentials improvement) [ 28 , 30 , 31 , 32 , 33 ].…”
Section: Nutrition Blood Nutrient Levels Of Oxidative Stress and Glau...mentioning
confidence: 99%
“… 82 These glaucoma supplements are also natural products, most of which have antioxidant and anti-inflammatory properties, and they are readily available and cost-effective. 106 Although a series of experimental studies and clinical trials have shown that these drugs exhibit IOP-lowering or optic neuroprotective effects, they still cannot replace conventional glaucoma drugs for stand-alone treatment. They need to be tested repeatedly and pass approval before they can truly become part of adjuvant glaucoma treatment.…”
Section: Sustained-release Drug Delivery Systems In Glaucomamentioning
confidence: 99%